Business Perfomance Evaluation of a Recreation Company in Indonesia Using Balanced Scorecard - Wendy Tandiawan (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: The purpose of this research is to conduct a business performance evaluation of Taman Impian Jaya Ancol (TIJA), a company with a unique type of business, which is recreation. TIJA, which used to be very crowded and became the pride of Jakarta, currently looks not crowded anymore. This research also aims to see TIJA’s current business condition, whether it is still good, and find out if there are things that can be improved. Methodology: This research is a case study research with qualitative and quantitative data. There are two (2) stages in this research, which are the objectives determination stage which is sought by conducting a SWOT Balanced Scorecard (BSC) analysis, and the analysis stage which is carried out with Balanced Scorecard. Results: The results show that TIJA's business is in the above average category, which means it is still good. Seeing this, there is still room for TIJA to improve in order to achieve a higher score. This research shows that innovation is the most important objective that must be further improved and developed.